First records of Diptera associated with human corpses in Ecuador - García-Ruilova, Ana (2020)
Flies in the order Diptera are of forensic value because many species leave tractable evidence while harvesting nutrients from decomposing corpses. From December 2015 to January 2017, 41 fly specimens were collected in human bodies at crime scenes and autopsies across the south of Ecuador. Six species, e.g., Chrysomya albiceps (Widemann 1819), Chrysomya megacephala (Fabricius, 1794), Synthesiomyia nudiseta (Wulp, 1883), Lucilia purpurascens (Walker, 1836), Hemilucilia segmentaria (Fabricius, 1805), and Stomoxys calcitrans (Linneo, 1758) were identified to species level using morphological (dichotomous keys) and molecular (mitochondrial COI barcodes) techniques. One additional specimen remains unidentified to species level, but COI barcodes assigned it to the genus Paralucilia. These first taxonomically curated records of flies in real cases constitute a tangible groundwork for the development of forensic entomology in Ecuador. © 2020 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.